220k views
4 votes
Let f(x) = 4x + 3 and g(x) = -2x + 5. Find (f.g)(5)

User MrRoy
by
5.2k points

1 Answer

4 votes

Answer:
(f*g)(5)=-115

Explanation:

Given the function f(x):


f(x) = 4x + 3

And the function g(x):


g(x) = -2x + 5

We need to multiply them in order to find
(f*g)(x). Then:


(f*g)(x) = (4x + 3)(-2x + 5)\\(f*g)(x)=-8x^2+20x-6x+15\\(f*g)(x)=-8x^2+14x+15

Now we must substitute
x=5 into
(f*g)(x)=-8x^2+14x+15. Then, we get that
(f*g)(5) is:


(f*g)(5)=-8(5)^2+14(5)+15\\(f*g)(5)=-115

User Janemarie
by
4.6k points